Game Edukasi Anak Usia Dini Berbasis Android Menggunakan Adobe Flash CS6 - Ani Hartati; Fajriyah Fajriyah; Khana Wijaya (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
In this method the author uses the UCD (User Centered Design) system development method and analysis and system design tools using a Flowchart (Flowchart) programming language used JAVA language with Adobe Flash CS6 application. This application was created aiming to be able to help early childhood, kindergarten/PAUD level students as well as teachers and parents in introducing and teaching letters, numbers, fruit, colors, animals, shapes and vehicles.